1942
DOI: 10.1002/cber.19420750906
|View full text |Cite
|
Sign up to set email alerts
|

Autoxydation von Kohlenwasserstoffen, VI. Mitteil. : Über Indan‐peroxyd

Abstract: Licht. Eine solche Messung wird an anderer Stellel) ausfiihrlich mitgeteilt. Weitere derartige Messungen ergaben an Zinkoxyd und Aluminiumoxyd iibereinstimmend folgendes : Die hohe Absorptionsbande des Uranyls bei Wellenlangen unterhalb 500 mp wird bei der Verfarbung nur unwesentlich erhoht, hauptsachlich wird die Absorption im Gebiet der niedrigen Banden zwischen 750 mp und 500 mp um rund 50% erhoht und gleichzeitig nivelliert. Die Geschwindigkeit der Absorptionszunahme steigt dabei im allgenieinen mit der We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1943
1943
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Hock and Lang (27) found that cyclopentene is oxidized at a slower rate than cvclohexene, and hydrindene, which can be regarded as tetralin minus one CH2 group, at a slower rate than tetralin; from these results they conclude that a five-membered ring is less readify oxidized than a six-membered ring. However, their conditions differed from those used by others quoted above in that they used oxygen plus ultraviolet light.…”
Section: B Mixtures and Petroleum Fractionsmentioning
confidence: 96%
“…Hock and Lang (27) found that cyclopentene is oxidized at a slower rate than cvclohexene, and hydrindene, which can be regarded as tetralin minus one CH2 group, at a slower rate than tetralin; from these results they conclude that a five-membered ring is less readify oxidized than a six-membered ring. However, their conditions differed from those used by others quoted above in that they used oxygen plus ultraviolet light.…”
Section: B Mixtures and Petroleum Fractionsmentioning
confidence: 96%
“…The saltlike organosodium peroxides are prepared by the reaction of an alkyl or aralkyl hydroperoxide with a concentrated solution of sodium hydroxide at room temperature (37,51,86,94,96,97,190). The sodium salt of a number of tertiary alkyl hydroperoxides, e.g., triphenylmethyl hydroperoxide, cannot be prepared by this method.…”
Section: Preparation Of Organosodium Peroxidesmentioning
confidence: 99%
“…Hartmann and later Hock and Susemihl 8 succeeded independently in the isolation of crystalline peroxide in the oxidation of tetralin at 70-80°C and identified it as -hydroperoxy tetralin. Hock and Lang showed that in the oxidation of indane 9 and from simple alkylaromatics like p-xylene 10 , ethylbenzene 10 and cumene 11 , the corresponding hydroperoxides as primary products could be isolated in which the -OOH group is present at the carbon atom at -position to the aromatic ring. IG-Farben processed a method for the oxidation of ethylbenzene 12 .…”
Section: Introductionmentioning
confidence: 99%